2020
DOI: 10.3390/cells9061374
|View full text |Cite
|
Sign up to set email alerts
|

Early Reperfusion Following Ischemic Stroke Provides Beneficial Effects, Even After Lethal Ischemia with Mature Neural Cell Death

Abstract: Ischemic stroke is a critical disease caused by cerebral artery occlusion in the central nervous system (CNS). Recent therapeutic advances, such as neuroendovascular intervention and thrombolytic therapy, have allowed recanalization of occluded brain arteries in an increasing number of stroke patients. Although previous studies have focused on rescuing neural cells that still survive despite decreased blood flow, expanding the therapeutic time window may allow more patients to undergo reperfusion in the near f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(87 citation statements)
references
References 68 publications
(142 reference statements)
7
80
0
Order By: Relevance
“…Of interest, consistent with a previous study [ 16 ], we found that larger numbers of neutrophils were present within ischemic areas after permanent ischemia compared with those of reperfusion after ischemia [ 25 ]. It has been documented that anoxia/reperfusion injuries promote the adherence of neutrophils to endothelial cells in vitro and that several cell adhesion molecules (e.g., intercellular adhesion molecule 1, vascular cell adhesion molecule 1, E-selectin, and P-selectin) play an important role in neutrophil migration into endothelial cells [ 31 , 36 , 37 ].…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Insupporting
confidence: 92%
See 4 more Smart Citations
“…Of interest, consistent with a previous study [ 16 ], we found that larger numbers of neutrophils were present within ischemic areas after permanent ischemia compared with those of reperfusion after ischemia [ 25 ]. It has been documented that anoxia/reperfusion injuries promote the adherence of neutrophils to endothelial cells in vitro and that several cell adhesion molecules (e.g., intercellular adhesion molecule 1, vascular cell adhesion molecule 1, E-selectin, and P-selectin) play an important role in neutrophil migration into endothelial cells [ 31 , 36 , 37 ].…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Insupporting
confidence: 92%
“…Recently, Tachibana et al demonstrated that reperfusion following lethal ischemia had beneficial effects such as neurological functional recovery in a mouse model of stroke [ 16 ]. More recently, with the use of a highly reproducible mouse model of middle cerebral artery occlusion (MCAO) [ 14 , 29 , 30 ], we investigated whether reperfusion during stage II can have beneficial effects at acute (1–7 days after MCAO) and chronic (more than 3 weeks after MCAO) periods by focusing on histology and brain function [ 25 ].…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Inmentioning
confidence: 99%
See 3 more Smart Citations